Exogenous Shocks and Growth Crises in Low-Income Countries : A Vulnerability Index - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2012)
This paper develops a new index which provides early warning signals of a growth crisis in the event of large external shocks in low-income countries. Multivariate regression analysis and a univariate signaling approach are used to map information from a parsimonious set of underlying policy, structural, and institutional indicators into a composite vulnerability index. The results show that vulnerabilities to a growth crisis in low-income countries declined significantly from their peaks in the early 1990s, but have risen in recent years as fiscal policy buffers were expended in the wake of the global financial crisis.a.